Penguatan Kompetensi Profesional Guru Matematika Madrasah Tsanawiyah di Kota Mataram dalam Pembelajaran Geometri Melalui Pelatihan Pemanfaatan Tools Program GeoGebra - Rusadi, Tri Maryono; Satriyantara, Rio; Robbaniyyah, Nuzla Af’idatur; Abdurahim, Abdurahim; Marwan, Marwan; Syamsul Bahri; Aini, Qurratul; Irwansyah, Irwansyah; Syechah, Bulqis Nebula; Salwa, Salwa; Awalushaumi, Lailia; Alfian, Muhammad Rijal; Maharani, Andika Ellena Saufika Hakim; Kurnia, Agus; Hidayat, Malik; Kusuma, Shendy Arya; Zikri, Lalu Muhammad Faiz (Puslitbang Sekawan Institute Nusa Tenggara, 2025)
This community service program was carried out with the primary objective of enhancing the professional competence of mathematics teachers at the Madrasah Tsanawiyah (MTs) level in Mataram City, particularly in the teaching of geometry. Recognizing the importance of mastering digital technology in modern mathematics learning, the program focused on the introduction and application of GeoGebra as an interactive medium for teaching geometry concepts. The activities were conducted at the Basic Computer Laboratory of the Faculty of Mathematics and Natural Sciences, Universitas Mataram, involving 18 MTs mathematics teachers. The program consisted of introducing fundamental concepts of geometry, hands-on training on the technical use of GeoGebra, and an evaluation of learning outcomes through pre-tests and post-tests. The evaluation results indicated an improvement in participants’ scores, demonstrating the effectiveness of the training. The teachers’ enthusiasm was evident from their active participation in discussions, asking questions, and exploring GeoGebra’s features during the training. The pre-test results showed that participants scored between 7 and 20, with an average of 13.56. Following the post-test, scores improved significantly, ranging from 20 to 28 with an average of 24.89. This confirms that all teachers, without exception, experienced an increase in scores. The positive impact of this program is expected to contribute to improving the quality of mathematics teaching at the MTs level.